Human Capital Management in the Philosophy of Progressivism - Dewi Sartika; Ahmad Rifa’i; Muhammad Shabibur Rahmat; Adib Habibi; Alda Syafira (Journal of Science and Research, 2025)
This paper examines the relationship between Human Capital Management (HCM) and the philosophy of progressivism in education. Progressivism, as developed by John Dewey, emphasizes learner-centered education, rejecting rigid traditional approaches while promoting active learning experiences as essential preparation for social life. Rooted in pragmatism, progressivism highlights practical benefits, flexibility, and the role of human intellect in problem-solving. Thus, education is not merely the transfer of knowledge but a process of holistic human development—intellectual, moral, and social—enabling individuals to adapt to changing times. This research uses a qualitative approach with a library research approach. This approach was chosen because the discussion focuses on a conceptual analysis of the philosophy of progressivism and its relationship to the concept of Human Capital Management in education. Data analysis was conducted in three stages: data reduction, data presentation, and conclusion drawing. In the context of modern educational management, progressive ideas strongly align with Human Capital Management. HCM positions humans as the primary capital to be developed through investment in education, skills, character, and well-being. The process includes planning, implementation, and evaluation strategies to ensure that individual potential creates added value for both organizations and society. The integration of progressivism and HCM affirms that educational management must focus on optimizing learners’ potential to be adaptive, productive, and responsive in facing global challenges.